Active thermographic inspection of carbon fiber reinforced plastic laminates using laser scanning heating. (1st February 2019) - Ishikawa, Masashi; Ando, Masaki; Koyama, Masashi; Nishino, Hideo
Abstract: In this study, inspection capability of active thermographic nondestructive inspection using the laser scanning method was examined. Carbon fiber reinforced plastic (CFRP) specimens were heated using a CO2 laser scanning device and their inspection capability was investigated. The experimental results indicate that the temperature and phase behavior after laser scanning heating were similar to those after conventional instantaneous flash heating. We also investigated the effect of the relationship between the scanning direction and fiber direction of the tested CFRPs on defect detection. The numerical and experimental results showed that the observed temperature contrast appearing on the defective surface varied depending on the scanning direction, and the temperature contrast increased when the scanning direction was the same as the fiber direction of the laminates. In addition, it was found that defects in a CFRP specimen located 10 m from the heat source could be detected using the laser scanning heating. These results suggest that using the laser scanning heating method is effective to inspect large objects located at far distances.